TINJAUAN YURIDIS MENGENAI PERDAGANGAN ORANG DARI PERSPEKTIF HAK ASASI MANUSIA - Yohanes Suhardin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Indonesia have regulated the trafficking since the Criminal Code (KUHP) era, the Act 39 of 1999 concerning Human Rights, the Act 23 of 2002 about Protection Child until currently we have the Act 21 of 2007 concerning Trafficking in Persons. However, the trafficking in persons cases increase dramatically and the law enforcement of trafficiking in persons was not function well. There are caused by some factors such as: the lack of sanction, the lack awareness of society, lack socialization of Trafficking in persons, and lack of victim awareness reporting the trafficking in person’s case to the police. From the social perspetive, the poor condition of the victim also become crusial factor caused weak of the law enforcement of trafficking in persons. Trafficking in persons in reality is not only breaking the Act 21 of 2007 and others trafficking in persons regulation but also tend to against the principle humiliated standard and human dignity and against of the human rights.